Innovations in Language Education in the Digital Era: Integrating AI, Pedagogy, and Cross-Cultural Learning in the 21st Century - Della Rahmayani; Azzahra Sindhi Latifa; Muhammad Nabil Fahmi; Miftahul Rohmah (2025)
The digital era has transformed language education, demanding not only linguistic proficiency but also the integration of digital literacy and intercultural communicative competence (ICC). This study addresses the fragmented nature of previous research by conducting a Systematic Literature Review (SLR) to analyze innovations in technology-enhanced language learning. The research aims to synthesize existing insights to propose a holistic pedagogical model. The study is grounded in three key frameworks: Communicative Language Teaching (CLT), digital literacy, and Byram's model of ICC, with an emphasis on the catalytic role of Artificial Intelligence (AI). The methodology involved a thematic analysis of international journals, conference proceedings, academic books, and official reports. The data collection and selection process adhered to a rigorous SLR protocol to ensure consistency and reproducibility. The findings reveal three main themes: (1) Pedagogical innovations often lack cohesive integration of digital practices and ICC; (2) Digital tools are widely used in higher education, yet ICC development remains underdeveloped; and (3) AI significantly enhances digital literacy and intercultural collaboration, but teacher intervention is crucial to overcome its dialogical limitations. Based on these findings, the study proposes a digital collaborative storytelling model that integrates CLT, digital literacy, ICC, and AI. This model offers an innovative approach to foster interactive, reflective, and culturally meaningful language learning. The research contributes to developing a more holistic, adaptive, and sustainable 21st-century language pedagogy.